Energy efficiency enhancement using dynamic voltage restorer (DVR) - Othman, Muhammad Murtadha; Nek Rakami, Nik Muhamad Lokman Fahmi; Abdul Hamid, Zulkiffli; Musirin, Ismail; Othman, Mohammad Lutfi (Institute of Advanced Engineering and Science, 2019)
Dynamic voltage restorer (DVR) is a device that can compensate harmonic, voltage sag and voltage swell condition that exists in a three-phase system. Other than that, DVR can also be used to enhance the energy efficiency or energy saving by reducing excessive amount of incoming power via the reduction incoming voltage at allowable limit. The DVR can inject the required voltage in the system so that the interruption of supply voltage can be compensated. The compensation of voltage supply interruption is improved based on the hysteresis voltage output of controller used in the DVR to detect the difference between reference voltage and disrupted voltage. The hysteresis voltage control mainly controlled by relays switching so that the signal can be sent to IGBT switches controller. The hysteresis voltage control and unipolar SPWM is supplied to control the IGBT switches by the DC supply for voltage interruption compensation. The unipolar SPWM technique converts the DC supply voltage into AC supplied voltage, thus making the DVR injection become easier to inject the AC voltage into the system to compensate voltage sag and voltage swell.